Instructor enthusiasm in online lectures: how vocal enthusiasm impacts student engagement, learning, and memory - Marty-Dugas, Jeremy; Rajasingham, Maya; McHardy, Robert J.; Kim, Joe; Smilek, Daniel (Frontiers in Education, 2024)
Across two studies we investigated the impact of instructor enthusiasm on student attentional engagement during an online undergraduate lecture, as well as their memory for lecture content and their motivation to watch additional lecture videos on the same topic (Study 2 only). In both studies participants were randomly assigned to watch a 22-minute lecture, delivered with either high or low vocal enthusiasm by the instructor. Subjective ratings of instructor enthusiasm/energy confirmed that in both studies the manipulation of instructor enthusiasm was effective. More importantly, in both studies we found that students in the high enthusiasm condition were consistently more engaged over the course of the lecture compared to those in the low enthusiasm condition, and that overall, reports of engagement increased together with ratings of instructor enthusiasm. However, we found no evidence that instructor enthusiasm influenced quiz performance in either study. Nevertheless, Study 2 showed that those in the high enthusiasm condition were more motivated to watch the next lecture than those in the low enthusiasm condition. These findings make an important contribution to the study of online learning and indicate that instructor enthusiasm may be a viable strategy to increase student engagement and motivation in online courses.